Super Rabbit Boy's team-up trouble! - Flintham, Thomas (2021)
When King Viking, Miss Business, and their henchmen team up to cause trouble, Super Rabbit Boy and Mega Mole Girl also join forces, but will they be able to work together to save the world?
Ages 6-8.
Grades K-1.
Keywords: Superheroes -- Fiction; Supervillains -- Fiction; Animals -- Fiction; Video games -- Fiction